The interrelationship of physical fitness, somatotype, body cathexis and personality in a group of white schoolboys - Fieldsend, Jeremy Rowell (Rhodes University, Faculty of Science, Department of Human Movement Studies, 1980)
The evaluation of physical fitness is dependent upon the body and its capacity to generate requisite degrees of strength, speed, mobility and endurance, for effective physical performance. The physical properties of the body, and in particular the degree of muscularity and adiposity, are affected substantially by varying levels of physical fitness. This degree of muscularity and adiposity is closely related to the shape or physique of the body, which in turn, can influence the attitudes an individual adopts toward his body and himself (body cathexis). The purpose of this study was to investigate the reciprocal relationship between physical fitness, somatotype (physique) and body cathexis (satisfaction). A secondary objective was to examine the relationship between these variables and personality. The subjects who participated in this study were white schoolboys completing Standard Eight. Seventy seven subjects, all of whom were either 14 or 15 years of age, were studied. A total of 22 observations were made on each subject, which included a battery of physical fitness tests, anthropometric and somatotypological observations, and two questionnaires. Fleishman's Basic Fitness Test battery, which was slightly modified, was utilized to evaluate the subjects' level of physical fitness. Standardized anthropometric techniques and equipment were used to measure heights, mass, diameters, girths, and skinfolds. These basic anthropometric observations were then utilized to determine the subjects' Heath-Carter somatotype rating, absolute and relative body fat, and lean body mass. Body cathexis was measured by the Secord-Jourard Body Cathexis Scale and personality was assessed by the Howarth personality Questionnaire. The results indicated that physical fitness performance on the events which required the body mass to be displaced were highly and negatively related to the degree of excess adipose tissue. Significant differences in endomorphy (p < 0,005) were apparent in high and low fit groups, but no somatotypological differences were indicated for those events which did not involve the displacement of the body mass. The one exception to this was a static strength event, in which significant somatotypological differences between high and low fit groups were indicated for mesomorphy (p < 0,005) and ectomorphy (p < 0,01). Body cathexis was not closely related to physical fitness, somatotype, or personality. A number of weak relationships were apparent: there was a negative correlation between body cathexis and the personality trait of inferiority; high levels of adipose tissue negatively influenced the level of body cathexis; and good performance on the strength events was positively associated with body cathexis. In the physical fitness events requiring strength and the body mass to be displaced, the body cathexis levels of high fit subjects exceeded that of low fit subjects at a statistically significant level (p < 0,005). No significant differences in body cathexis were indicated for those events which did not require the displacement of the body mass. Personality was not related to physical fitness, somatotype or body cathexis. The only relationship that was discerned was the low correlation between inferiority and body cathexis . The findings of this investigation suggest that, in this context, dynamic physical fitness performance, is closely related to physique; and in particular a high endomorphic content is a limiting factor. Body cathexis is not closely related to physical fitness, somatotype or personality. It is likely, however, that feelings of inferiority and excess adipose tissue are associated with a low body cathexis, while strength is related to a high body cathexis. Personality is not related to physical fitness, physique or body.
Keywords: Somatotypes -- Psychological aspects; Physical fitness for children -- Psychological aspects